Investigating the Impact of AI Tools on English Mastery at SMP Muhammadiyah Tanjungpinang - Risgar Friassantano; Nanda Kristia Santoso; Marina Lidya; Leona Patria Devi (CV. Ulil Albab Corp, 2026)
The integration of Artificial Intelligence (AI) in education has significantly transformed English language learning by offering more flexible, accessible, and personalized learning experiences. However, the increasing use of AI tools also raises concerns regarding students’ critical thinking and learning autonomy. This study aims to investigate the impact of AI on English language learning at SMP Muhammadiyah Tanjungpinang, explore teachers’ perspectives, and examine the roles of teachers and parents in guiding AI use. This research employs a qualitative-dominant mixed methods design, involving three English teachers and thirty students from grades 7, 8, and 9. Data were collected through semi-structured interviews, questionnaires, and observation, and analyzed using thematic analysis and descriptive statistics. The findings reveal that while AI enhances learning efficiency and provides immediate support for language tasks, students tend to rely on it primarily for completing assignments without critical evaluation. This reliance may reduce cognitive engagement and hinder the development of independent learning skills. Teachers acknowledge the benefits of AI but express concerns about students’ overdependence and highlight the need for professional training. Additionally, parental awareness of AI remains limited, affecting effective supervision at home. The study concludes that AI should be positioned as a complementary learning tool, supported by active guidance from teachers and parents to foster critical, ethical, and reflective learning practices.